IMPLEMENTASI TOTAL QUALITY MANAGEMENT PENDIDIKAN MELALUI USWAH HASANAH PADA TK-IT UMAR BIN KHATHAB KUDUS - Ulyani, Himmatul (QUALITY, 2019)
This research is motivated by the number of guardians of students who become workers from the morning until noon in the afternoon, and the progress of the times is very rapid with globalization they want the fulfillment of children's rights to get general and religious education in a quality management institution. The results of this study are as follows: (1) The concept of applying TQM at TKIT Umar Bin Khathab Kudus, internal and external analysis, evaluating school programs conducted at the beginning and end of the semester, principally; active participation of all parties, quality oriented based on user satisfaction, top down and bottom up management dynamics, instilling a culture of "team work" well, instilling a culture of problem solving through the concept of PDCA (Plan-Do-Check-Action), and continuous improvement. (2) Implementation of TQM education in the development of curricula with the approach of hasanah at TKIT Umar bin Khathab Kudus; focus on customers, total involvement, measurement, commitment, continuous improvement, (3) the role of TQM education in improving organizational performance with the approach of hasanah prayer at TKIT Umar bin Khathab Kudus; obsession with quality, scientific approach, teamwork, education and training, controlled freedom, unity of purpose. Keywords: Total Quality Management; Uswah Hasanah; TKIT